HUBUNGAN JENIS PEKERJAAN IBU DENGAN PEMBERIAN ASI PADA BAYI DI PUSKESMAS RANOMUUT MANADO - Koba, Edward R.; Rompas, Sefti S.; Kallo, Vandri D. (JURNAL KEPERAWATAN, 2019)
Abstract : Exclusive breastfeeding is not giving the baby food or other drinks, other than breastfeeding. Work is generally a time-consuming activity for the mother. One of the causes of the failure of exclusive breastfeeding is working mothers. The purpose of this research was to determine the relation between the type of work of mothers with exclusive breastfeeding to infants at Ranomuut Manado Health Center. Research Design This type of research uses an analytical survey type with a cross sectional approach. The number of samples is 39 people using purposive sampling technique. The data was collected using by questionnaire. The analysis of the data using Pearson Chi-square statistical test. The results showed that mothers with the most types of work were IRT (51.3), most babies received exclusive breastfeeding for (48.7%) and the results of statistical tests obtained p = 0.024 <0.05. The Conclusion of this research are there is a correlation between the type of work of mothers with exclusive breastfeeding for infants at Ranomuut Manado Health Center.Keywords: Type of works, Exclusive Breastfeeding.Abstrak : Menyusui eksklusif adalah tidak memberikan bayi makanan atau minuman lain, selain menyusui. Bekerja umumnya merupakan kegiatan yang menyita waktu bagi ibu. Salah satu penyebab belum berhasilnya pemberian ASI Eksklusif adalah ibu bekerja. Tujuan Penelitian ini bertujuan untuk mengetahui hubungan jenis pekerjaan ibu dengan pemberian ASI Eksklusif pada bayi di Puskesmas Ranomuut Manado. Desain Penelitian Jenis penelitian ini menggunakan jenis penelitian survey analitik dengan pendekatan cross sectional. Jumlah sampel 39 orang dengan menggunakan teknik sampel purposive sampling. Alat pengumpulan data berupa kuesioner. Analisa data menggunakan uji statistic Pearson Chi-square. Hasil Penelitian didapatkan bahwa ibu dengan jenis pekerjaan paling banya yaitu sebagai IRT (51,3), sebagian besar bayi mendapatkan ASI Eksklusif sebesar (48,7%) dan hasil uji statistic didapatkan nilai p = 0,024 < 0,05. Kesimpulan ada hubungan jenis pekerjaan ibu dengan pemberian ASI Eksklusif pada bayi di Puskesmas Ranomuut Manado. Kata Kunci : Jenis Pekerjaan ibu, ASI Eksklusif